Influência do estilo de uso da informação proporcionada pelo SCG no desenvolvimento do capital intelectual - Novas, Jorge (2013)
This research uses organizational data obtained from the development and application of a survey and the structural equation modeling to assess whether the dynamic tension between diagnostic and interactive use of management accounting systems (MAS) favors the development of intellectual capital (IC) and, if so, how this effect has an impact on performance. The results show that this dynamic tension underlying contemporary MAS is likely to support relational schemas that favor the development of the IC, with a positive impact on performance. The results are relevant as they clarify the usefulness of broad use of the MAS to sponsor the maintenance and development of relational schemas that underlie the creation of IC with positive impact on performance. The work offers an approach that also focuses on behavioral aspects and styles of leadership as, as shown, it is the use of MAS and the information it provided, and not necessarily its configuration, which gives it a more or less diagnostic/interactive nature.